Pathology of nerve cell membranes in complicated and severe human brain traumatic injuries. An electron microscopic study using cortical biopsies - Castejón, Orlando J. (Revista de la Universidad del Zulia, 2020)
Cortical biopsies of ten patients with severe and complicated brain traumatic injuries were examined with transmission electron microscope to study the ultrastructural damage of nerve cell membranes. The nonpyramidal neurons, astrocytes and oligodendrocytes showed plasma membrane fragmentation and areas of focal necrosis, enlargement and degranulation of rough and smooth endoplasmic reticulum cisterns, Golgi complex membrane fragmentation, and irregular dilation and disasembly of nuclear envelope. The degenerated myelinated axons showed invaginations and fragmentation of axolemmal membrane, and myelin sheath vacuolization. Synaptic disassembly and disruption and disassembly of interastrocytary gap junctions were also found. Disruption of neuronal Ca2+ homeostasis, activation of phospholipases and calpain, peroxidative stress, hemoglobin cytotoxicity, glutamate cytotoxicity, and ischemia of brain parenchyma are discussed in relation with the nerve cell membrane damage.